KONSEP FIQH SIYASAH DALAM PERATURAN PEMERINTAH NOMOR 10 TAHUN 1983 JO. NOMOR 45 TAHUN 1990 - Siti Mahmadatun (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2017)
Each country has a political system in his country respectively. The political system is adopted that will affect the wheels of government in the country. The political system is always changing according to the situation of economic, community, social style and other external factors that can affect the country. In Indonesia alone, the system of government has undergone three changes. early period called the era of the old order, after President Sukarno to resign from office and replaced by President Sueharto bergantilah Become the New Order era, and setealh 1998 with called reform era. Government Regulation No. 10 of 1983 and No. 45 of 1990 which created the new order have been qualified fiqh siyasyah Yang expressed by Abd Rahman Taj. Government Regulation No. 10 of 1983 and No. 45 of 1990 also contains values that refer to maslahah maslahah expressed by Imam Malik. In another sense that Inside Government Regulation No. 10 of 1983 and No. 45 of 1990 There is a concept that has a goal of fiqh siyasyah maslahah for Civil Servants (PNS) in particular and to society in general.